Ice Adhesion Tests on Coatings Subjected to Rain Erosion - Minsk, L. D. (1980)
Screening tests to select ice phobic coatings displaying low ice release forces, both before and after exposure to rain erosion in a whirling arm simulator, were performed on approximately 60 commercial materials. A unique linear ball-slide shear test apparatus was designed to provide pure shear forces. No coating survived the erosion test to give an interfacial shear strength as low as 15 psi (103 kPa), an arbitrarily established goal. Several coatings showed shear strengths between 30 and 45 psi (207 and 310 kPa) after rain erosion.